KEBIJAKAN KERUKUNAN ANTAR UMAT BERAGAMA DI DESA BALUN, KAB. LAMONGAN - Farah Damayanti (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2020)
Indonesian society has local cultures and traditions that are functionally able to maintain the environment situation in order to remain harmonious, both with fellow humans and the environment. These local traditions have important meanings and values, among others, as a reference for the behavior of the people in living their lives, including facing differences in interacting with different people culture. These local traditions are actually the expression of local knowledge or local wisdom of a community in response to their environmental situation. Balun Community Balun Village, Turi Subdistrict, Lamongan Regency is able to maintain religious harmony, even though they have different religions. This is due to the existence of elements which become social glue in the form of local wisdoms that live in Balun society. Substantially, local wisdom is the values ​​that apply in a society. These values ​​are believed to be true and become a reference in the daily behavior of the local community. These values ​​of local wisdom are seen as entities that determine the dignity and human dignity of the community because they contain elements of creative intelligence and local knowledge from the elites and their communities.